Comparison of Consumer Dispute Resolution of Car Purchases on Credit in Indonesia, Malaysia and Australia - Sri Wahyuni; Efa Laela Fakhriah; Anita Afriana; Sonyendah Retnaningsih (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Consumer protection in car credit financing requires effective dispute resolution mechanisms. Specific Background: Indonesia, Malaysia, and Australia apply different legal and institutional approaches to resolving consumer disputes. Knowledge Gap: Comparative evidence on the strengths and weaknesses of these systems remains limited. Aims: This study compares consumer dispute resolution mechanisms for car credit purchases in the three countries. Results: Using normative legal research with statutory, case, conceptual, and comparative approaches, the study found that Indonesia faces overlapping institutional authority, Malaysia provides a simpler tribunal-based mechanism, and Australia adopts preventive protection through hardship notices and the Australian Financial Complaints Authority. Novelty: The study integrates institutional authority, procedural simplicity, legal certainty, and preventive protection into a comparative framework across three different legal systems. Implications: Strengthening institutional authority, simplifying procedures, and adopting preventive consumer protection mechanisms may improve legal certainty in Indonesia. Highlights: Indonesia experiences overlapping institutional authority in dispute resolution. Malaysia applies a streamlined tribunal-based settlement system. Australia emphasizes preventive consumer protection through external dispute resolution. Keywords: Car Loan Purchase, Consumer Protection, Dispute Resolution, Legal Comparison